Modeling Requirements for Computer Simulation of Cerebral Aneurysm. (16th February 2014) - Ghodsi, S. R.; Esfahanian, V.; Ghodsi, S. M.
Abstract : Background . In order to reduce the mortality risk of aneurysm rupture, a timely diagnosis and treatment are vital. There are different reasons for aneurysm, such as hypertension, arteriosclerosis, and heredity. An efficient and cost-effective method to study the generation, development, and rupture of aneurysm and also analysis of treatment methods can accelerate progress. The Computational Fluid Dynamics is a well-known tool to simulate various phenomena. A reliable virtual modeling in biology depends on our knowledge about variety of characteristics, that is, biological features, structural properties, and flow conditions. Objective . Because of the vast research about the related subjects, an organized review is required. The aim of current review article is classification of the required foundations for a reliable virtual modeling of cerebral aneurysm, especially in the Circle of Willis.